2008
DOI: 10.1002/ajmg.b.30850
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between SAT‐1 −1415T/C polymorphism and anxiety

Abstract: Limbic glutamatergic neurotransmission plays a pivotal role in the pathogenesis of anxiety disorders. Polyamines modulate the activity of several ionotropic glutamate receptors and have been involved in the regulation of fear-conditioning response. Spermidine/spermine N1-acetyltransferase (SSAT-1) is the main enzyme regulating polyamine catabolism. The aim of the present study was to examine the association between anxiety disorders and the -1415T/C (rs1960264) single nucleotide polymorphism (SNP) of the gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
1
13
0
3
Order By: Relevance
“…The effect of other potential confounding factors, such as age or alcohol consumption, was not investigated. The population that we have investigated in a previous study (12) showed similar genotypic frequencies of SSAT1. However, due to missing values in the diagnosis of AUD, we were unable to assess the relationship of AUD to SSAT1 genotypic frequencies in this previous sample.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The effect of other potential confounding factors, such as age or alcohol consumption, was not investigated. The population that we have investigated in a previous study (12) showed similar genotypic frequencies of SSAT1. However, due to missing values in the diagnosis of AUD, we were unable to assess the relationship of AUD to SSAT1 genotypic frequencies in this previous sample.…”
Section: Discussionsupporting
confidence: 53%
“…Genetics analysis was performed following the method previously described by our group (12). Briefly, PCR amplification of a 298 bp fragment from the promoter region of the SSAT1 gene containing the -1415 T/C polymorphism (rs1960264) was carried out.…”
Section: Genotype Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropsychiatric Genetics [Vaquero-Lorenzo et al, 2008]. One of these variants, rs6926342, was also found to be associated with SAT1 expression in several brain regions.…”
mentioning
confidence: 95%
“…Moreover, as the D allele is on the same haplotype as the C risk allele of rs6526342, our results add further weight to the importance of this haplotype in suicide completion. Interestingly, this haplotype also includes the T allele of rs1960264, which has been found to be significantly associated with anxiety disorders [Vaquero-Lorenzo et al, 2008]. Given the high LD among promoter variants, these associations may all reflect the involvement of a single polymorphism in increasing the susceptibility to suicide and anxiety.…”
mentioning
confidence: 97%